The relationship between the use of mobile applications and job performances among employees in unit of transportation at Universiti Malaysia Perlis (UniMAP)./ Fadhilah Aisyah Ramli - Ramli, Fadhilah Aisyah (2018)
The topic of this study is “The Relationship between the Use of Mobile Applications and Job Performance among Employees in Unit of Transportation at Universiti Malaysia Perlis (UniMAP)”. Technology acceptance model such as the use of mobile application have a big impact on job performance of employees. The objective for this study is to investigate the relationship between perceived usefulness, perceived ease of use and behavioral intentions to use mobile applications (WhatsApp) and job performance among employees in Unit of Transportation at Universiti Malaysia Perlis (UniMAP). This study focused on 105 employees in Unit of Transportation at Universiti Malaysia Perlis (UniMAP), Perlis. The method used by the researcher to collect data was questionnaires. On 23rd March 2018, the researcher had distributed 105 set of questionnaires and on 29th March 2018, the questionnaire had been returned to the researcher. The result shows that the average of the respondents agreed that the variables of mobile applications influence job performance among employees in Unit of Transportation at Universiti Malaysia Perlis (UniMAP).Therefore, some recommendations have been provided by the researcher for organization, employees and future researcher have been highlighted for future study.